Current approach to diagnosis and treatment of focal nodular hyperplasia in children with a management algorithm - Chudoba, Anna; Pawłowska, Joanna; Cielecka-Kuszyk, Joanna; Majak, Dorota; Jankowska, Irena; Broniszczak-Czyszek, Dorota; Barański, Jakub; Czubkowski, Piotr (Clinical and Experimental Hepatology, 2025)
Focal nodular hyperplasia (FNH) is a benign tumor of the liver rarely reported in children. It requires differentiation from malignant liver lesions, which are more common in the pediatric population. The pathogenesis of the disease remains unknown, but previous oncological treatment of non-liver neoplasms or vascular abnormalities may predispose to FNH development. Differential diagnosis is based on radiological imaging with rare indications for diagnostic biopsy or resection. There are no specific management guidelines for FNH in children, but in most cases watchful waiting is most appropriate. In symptomatic, rapidly growing cases, surgical or radiological intervention may be considered. In this review, we present the clinical features, natural course, and current management patterns in pediatric FNH. Key words: children, diagnosis, management, FNH, focal nodular hyperplasia.